2009
DOI: 10.1111/j.1399-0012.2009.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced post‐operative neutrophil activation in liver transplant recipients suffering from post‐hepatitic cirrhosis

Abstract: The results of this study suggest a reduced post-operative neutrophil activation in liver transplant recipients suffering from post-hepatitic cirrhosis compared to cirrhosis due to other causes. We hypothesized that neutrophil dysfunction in those patients depends on the underlying disease with an increased susceptibility to bacterial or fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…In other studies, persistent cellular defects were also observed 12. An impaired RB of PMN was also reported in liver transplant recipients suffering from posthepatitic cirrhosis 13…”
mentioning
confidence: 64%
“…In other studies, persistent cellular defects were also observed 12. An impaired RB of PMN was also reported in liver transplant recipients suffering from posthepatitic cirrhosis 13…”
mentioning
confidence: 64%
“…Patients with cirrhosis have impaired neutrophilic ROS production, as well as phagocytotic and microbicidal activities [ 176 , 177 , 178 ]. Post-hepatic cirrhosis has also been observed to be closely related to diminished ROS production in some liver transplant recipients [ 179 ]. The mechanism of impaired signaling events of neutrophils in relation to alcoholic cirrhosis is not fully understood.…”
Section: Role Of Myeloperoxidase In Different Diseasesmentioning
confidence: 99%
“…Of the numerous circulating host-defense mechanisms available, neutrophil production of ROS, microbicidal activity and phagocytosis are impaired in cirrhotic patients [27][28][29][30][31][32][33][34][35]. An impaired ROS production was also observed in liver transplanted recipients suffering from post-hepatitic cirrhosis [36]. However, the impact of alcoholic cirrhosis on receptor-mediated signaling events underlying neutrophil antibacterial activities remains largely unknown.…”
Section: Introductionmentioning
confidence: 97%